2014
DOI: 10.1111/jns5.12071
|View full text |Cite
|
Sign up to set email alerts
|

Painful neuropathies: the emerging role of sodium channelopathies

Abstract: Pain is a frequent debilitating feature reported in peripheral neuropathies with involvement of small nerve (Aδ and C) fibers. Voltage-gated sodium channels are responsible for the generation and conduction of action potentials in the peripheral nociceptive neuronal pathway where NaV 1.7, NaV 1.8, and NaV 1.9 sodium channels (encoded by SCN9A, SCN10A, and SCN11A) are preferentially expressed. The human genetic pain conditions inherited erythromelalgia and paroxysmal extreme pain disorder were the first to be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
78
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 108 publications
3
78
1
1
Order By: Relevance
“…The use of antisense, siRNA and murine mutations have indicated that impairment of Na v 1.3, 1.7,1.8 and 1.9 expression has varying antihyperpathic effects in models of inflammatory and neuropathic pain states [127,130,131]. Specific gain and loss of function mutations in the Na v 1.7 channels have been identified in humans wherein there is an increased and decreased pain state, respectively [132,133].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…The use of antisense, siRNA and murine mutations have indicated that impairment of Na v 1.3, 1.7,1.8 and 1.9 expression has varying antihyperpathic effects in models of inflammatory and neuropathic pain states [127,130,131]. Specific gain and loss of function mutations in the Na v 1.7 channels have been identified in humans wherein there is an increased and decreased pain state, respectively [132,133].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Its effects could also operate on the soma of C-fiber nociceptors that express VGKC currents, blockade of which could enhance neuronal excitability. Analogously, voltage-gated sodium channels were deemed responsible for the generation and conduction of action potentials in the peripheral nociceptive neuronal pathway where NaV 1.7, NaV 1.8, and NaV 1.9 sodium channels (encoded by SCN9A, SCN10A, and SCN11A) are preferentially expressed [33].…”
Section: Laboratory Investigation Of Vgkc Complex Autoimmunitymentioning
confidence: 99%
“…It affects the soma of C-fiber nociceptors that express VGKC currents, blockade of which could alter neuronal excitability. Analogously, voltage-gated sodium channels are responsible for the generation and conduction of action potentials along peripheral nociceptive neuronal pathways where NaV 1.7, NaV 1.8, and NaV 1.9 sodium channels are encoded by SCN9A, SCN10A, and SCN11A [134].…”
Section: Anti-vgkc-complex Encephalitismentioning
confidence: 99%